Ovotesticular differences of sex development: male or female? Case series - Maria-Grazia Scarpa; Arianna Lesma; Massimo Di Grazia; Waifro Rigamonti (BMC, 2019)
Abstract Background The choice of the sex of rearing in patients with ovotesticular differences of sex development (OT-DSD) is difficult. The final decision should be given by the patient himself or herself, but families' opinion is not to neglect especially when the diagnosis is precocious and the patient can't give the consent to medical or surgical procedures. How should we behave if the parents refuse to raise a child with genital ambiguity? Case presentation We describe and comment on our multidisciplinary approach in three patients with neonatal diagnosis of OT-DSD. The families expressed a strong desire for that which concerned the sex of rearing of their babies in contrast to the International trend of "wait and see". A specific counselling and a constant psychological support were given. Conclusions Recent trends suggest of postponing surgery to involve the patient in the decision. Child's well-being is the goal of therapy. When medical and psychological support is not able to force parents to accept a child suffering from genital ambiguity, we think that it is better to opt for reversible medical/surgical treatments rather than allowing patients to grow up within a family that does not accept them.